The Function of Code Mixing and Code Switching Uttered by Cinta Laura at Nebeng Boy William Youtube Channel - Amaniarsih, Dwi Suci; Juliana2, Juliana; Asrul, Nurmahyuni; Ginting, Erwin (EXCELLENCE: Journal of English and English Education, 2024)
Code mixing and code switching prove effective in navigating communication complexities arising from participant’ diverse linguistic proficiency levels. This article assesss the role of code mixing and code switching in the dialogue featuring Cinta Laura Kiehl on Boy William’s Youtube Channel, dated 6th September 2021, the titled is “#Nebeng Boy eps 42”. Employing a qualitative descriptive approach, the study gathers written data from Cinta Laura’s interview on Boy William Youtube Channel and analyzes it using explanatory samples. Cinta Laura, a proficient bilingual communicator, demonstrates the absence of language dominance. Specifically, the dominant function of code mixing relates to linguistic challenges, while code switching primarily involves the ability to articulate in a specific language. These findings aim to contribute to students’ English lecturers, and sociolinguistic researchers, encouraging a deeper exploration of the purpose behind code mixing and code switching in conversations.